(untitled) (Western Pacific Surveillance and Response, 2015)
For the first time in New Zealand, we report on the identification of Enterovirus C105 (EV-C105) from a 52-year-old male hospitalised with mild respiratory tract symptoms. Enterovirus (EV) serotyping was performed by partial sequencing of the VP1 region of the EV genome. This highlights the importance of enterovirus surveillance for detection of the importation of new genotypes such as EV-C105, thus allowing a better understanding of the roles they play in disease.